1974
DOI: 10.1002/food.19740180615
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über bittere Peptide aus Casein und Käse 1. Mitt. Stand der Kenntnisse

Abstract: Anhand eines Literaturiiberblickes mird der gegenwartige Stand der Kenntnisse iiber den Kasefehler ,,bitter" sowie iiber Bildung, Abbau und Struktur von bitteren Peptiden aus Casein dargelegt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1975
1975
2010
2010

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Another work of Wieser and Belitz (1976) further supported these results. Schalinatus and Behnker (1974) published a review of bitter peptides from casein and cheese. Arai et al (1970b) treated a bitter tasting hydrolysate with carboxypeptidases and found a reduction of the bitterness.…”
mentioning
confidence: 99%
“…Another work of Wieser and Belitz (1976) further supported these results. Schalinatus and Behnker (1974) published a review of bitter peptides from casein and cheese. Arai et al (1970b) treated a bitter tasting hydrolysate with carboxypeptidases and found a reduction of the bitterness.…”
mentioning
confidence: 99%